Medijski okviri protestniških gibanj v času pandemije covida-19 - Zupanc, Matej (Monitor ISH, 2023)
The article examines how the media framed the protests during the COVID-19 pandemic under the Janez Janša’s right-wing government. The protests movements were the result of the government’s decisions, the measures taken to contain the infection and the management of the epidemic. Using a deductive approach, the author identifies general frames in the media and inductively analyses content-specific frames related to the protests under study. In the article, he presents their occurrence in the newspaper Delo, the weekly Demokracija and the magazine Mladina. He then uses a qualitative analysis to illustrate the differences in framing between the selected media. On this basis, the author analyses the reasons for the differences in framing and identifies the factors contributing to this diversity in the coverage of the protests.
Keywords: Covid-19; Demonstracije; media; Mediji; pandemics; Pandemije; protests; SARS-CoV (virus)